Risk factors for intracranial hemorrhage and mortality in adult patients with severe respiratory failure managed using veno-venous extracorporeal membrane oxygenation. Issue 1 (5th January 2022) - Wu, Xiaojing; Li, Min; Cai, Ying; Zhai, Tianshu; Zhang, Yi; Zhan, Qingyuan; Gu, Sichao
Abstract: Background: Intracerebral hemorrhage (ICH) is one of the most severe complications during veno-venous extracorporeal membrane oxygenation (VV-ECMO). This study aimed to determine the risk factors for ICH and mortality in such patients. Methods: We analyzed the clinical data of 77 patients who received VV-ECMO due to severe respiratory failure from July 2013 to May 2019 at China-Japan Friendship Hospital. Demographical data, laboratory indices, imaging characteristics, and other clinical information were collected. Multivariable logistic regression analyses were performed to identify risk factors for ICH and mortality. Results: Of 77 patients, 11 (14.3%) suffered from ICH, and 36 (46.8%) survived. The survival rate was significantly lower (18.2% [2/11] vs . 51.5% [34/66], P  = 0.040) in patients with ICH than in those without ICH. Multivariable analysis revealed that factors independently associated with ICH were diabetes mellitus (adjusted odds ratio [aOR]: 12.848, 95% confidence interval [CI]: 1.129–146.188, P  = 0.040) and minimum fibrinogen during ECMO (aOR: 2.557, 95% CI: 1.244–5.252, P  = 0.011). Multivariable analysis showed that factors independently associated with mortality were acute hepatic failure during ECMO (aOR: 9.205, 95% CI: 1.375–61.604, P  = 0.022), CO2 retention before ECMO (aOR: 7.602, 95% CI: 1.514–38.188, P  = 0.014), and minimum platelet concentration during ECMO (aOR: 0.130, 95% CI: 0.029–0.577, P  = 0.007). Conclusions: Diabetes mellitus and minimum fibrinogen concentration during ECMO are risk factors for ICH in patients with severe respiratory failure managed using VV-ECMO. This indicated that anticoagulants use and nervous system monitoring should be performed more carefully in patients with diabetes when treated with VV-ECMO due to severe respiratory failure.